Experimental investigation into the effect of spindle rotational speed on surface roughness and mechanical properties of aluminium 6082T651 welded by friction stir process - M Pita (The international journal of multiphysics, 2023)
Selection of the correct parameters during the friction stir welding process is vital. The study entailed an analysis of the mechanical properties and microstructure of aluminium 6082T651 welded by friction stir welding at different spindle rotational speeds (500, 550, 600 and 650 rpm) and constant acceleration of 250 mm/min. Surface roughness of the welded samples was assessed according to ISO 25178. ASTM E384 and ASTM E8/E8M-09 standards were used for hardness and tensile tests respectively. The results show the highest tool rotational speed (650 rpm) to have produced the greatest weld surface roughness, of approximately 19.56 µm. The weldments made by friction stir welding at the highest tool rotational speed of 650 rpm displayed the best mechanical properties.